Geographical Indications and Legal Protections for Indonesian Livestock Products: A Critical Analysis of Policy and Enforcement - Listiasari, Faranita Ratih; Kuntari, Wien; Hastati, Dwi Yuni; Nuraeni, Ani (DiH: Jurnal Ilmu Hukum, 2025)
As an agricultural country, Indonesia has considerable potential for livestock products such as meat, eggs, milk, and processed products. Indonesia's biodiversity and vast territory produce livestock products with distinctive characteristics and uniqueness that differ from similar products made in different regions. To protect against counterfeiting of the origin of livestock products, these products are given markers known as Geographical Indications. This study aims to determine the criteria for livestock products to be registered for Geographical Indications and the benefits of protection of these Geographical Indications. The research method used is normative legal research, which analyzes laws, regulations, and other data to answer this research problem. Livestock products registered for Geographical Indications must be proven to have specific characteristics because of the conditions where the livestock products are produced. Climate, latitude, rainfall, and other factors can affect livestock products. The correlation between regional factors and livestock products brings products with specific characteristics that are different from similar products. Livestock products registered with Geographical Indications benefit consumers by avoiding livestock products not produced from the Geographical Indication area. For producers of livestock products, Geographical Indications are a promotional tool that can increase sales of their products. In addition, Geographical Indications help preserve the environment of the area where livestock products are produced so that the products do not change in quality or characteristics.